2018
DOI: 10.3897/phytokeys.110.28435
|View full text |Cite
|
Sign up to set email alerts
|

A Linnaeus NG interactive key to the species of Glomera (Orchidaceae, Coelogyninae) from Southeast Asia

Abstract: We present a multilingual interactive key available online (http://glomera.linnaeus.naturalis.nl) that can be used on any web browser without the need for installing additional software. The key includes 169 species of Glomera, a genus within the necklace orchids (Coelogyninae) not yet comprehensively treated in any recent field guide or web-based survey. With this key, plants can be identified using a combination of vegetative and floristic characters in addition to distribution and ecology as a first step to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Glomera is a genus that belongs in Coelogyninae tribe that is frequently overlooked because of their vegetative appearance resembles a small ericaceous plant. Glomera are characterized by elongated and branching stems with many leaves, stems enveloped by warty sheaths at the base, and ecological features particularly the distribution (Wati et al, 2018). In this study, only one species of Glomera was observed, there was Glomera papuana.…”
Section: The Notable Orchid Species Of Mount Binaiyamentioning
confidence: 55%
“…Glomera is a genus that belongs in Coelogyninae tribe that is frequently overlooked because of their vegetative appearance resembles a small ericaceous plant. Glomera are characterized by elongated and branching stems with many leaves, stems enveloped by warty sheaths at the base, and ecological features particularly the distribution (Wati et al, 2018). In this study, only one species of Glomera was observed, there was Glomera papuana.…”
Section: The Notable Orchid Species Of Mount Binaiyamentioning
confidence: 55%
“…From these, 14 specimens were collected in the field in Seram, Papua and Papua New Guinea (Indonesia). The first author also identified living orchid material from the Bogor Botanical Garden with identification keys and taxonomic descriptions from Schuiteman and de Vogel (2001), Wati et al (2018) and the website of de Vogel et al (2019). Additionally, a total of 42 specimens from the living orchid collection of the Hortus botanicus Leiden, Netherlands were analysed.…”
Section: Antimicrobial Activity Of Plants Extractsmentioning
confidence: 99%